Women in Surgery – Publication Activity in German University Departments of General and Visceral Surgery - C, Bockmann Eva; ES, Debus; RT, Grundmann (Archives of Clinical and Medical Case Reports, 2021)
Background: Women holding management positions in German university visceral and general surgery departments were registered and their publication performance compared to that of men. Methods: All PubMed-listed publications published by chief or consultant physicians as first or last author in the 10 years preceding 2017 were registered, as was the publication’s impact factor (IF). The cumulative impact factor acquired by each managing surgeon over the 10 year period was also totaled. Staffing was drawn from department websites as of July 1, 2017. Results: On this date 442 surgeons were employed in management positions (chief and consultants) at 38 university departments, 365 men (82.6%), 77 women (17.4%). Three department chiefs were women (7.9%). On average, management teams consisted of 11.6 surgeons / department, including 2 female surgeons. In 9/38 departments (23.7%) the proportion of managing women averaged 37.4%. In 8 departments (21.1%) no female surgeons held management positions. A total of 5363 first and last authorships were registered. The proportion of women holding authorship was 8.7%, with a cumulative IF of 7.0%. Only 59.7% of the women but 83.6% of the men had published. Compared to men, women achieved only half the cumulative IF (48.3 vs. 24.1, respectively). The average IF of individual publications was 2.4 for women and 3.0 for men. Conclusions: The present study confirms a strong preponderance of men in academic visceral surgery. However, in nine of 38 departments the gender ratio was largely balanced. This does indicate a tendency towards revision of the traditional male dominance in university surgery.